2015
DOI: 10.1002/stem.1871
|View full text |Cite
|
Sign up to set email alerts
|

Comparative FAIRE-seq Analysis Reveals Distinguishing Features of the Chromatin Structure of Ground State- and Primed-Pluripotent Cells

Abstract: Both pluripotent Embryonic Stem Cells (ESCs), established from preimplantation murine blastocysts, and Epiblast Stem cells (EpiSCs), established from postimplantation embryos, can self-renew in culture or differentiate into each of the primary germ layers. While the core transcription factors (TFs) OCT4, SOX2, and NANOG are expressed in both cell types, the gene expression profiles and other features suggest that ESCs and EpiSCs reflect distinct developmental maturation stages of the epiblast in vivo. Accordin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 70 publications
1
11
0
Order By: Relevance
“…Comprehensive mapping of open chromatin regions using FAIRE-seq in 2i-grown ESCs, EpiSCs, NPCs, and MEFs revealed a marked difference between the two pluripotent cell lines, ESCs and EpiSCs, and the two differentiated cell types (Murtha et al, 2015). ESCs and EpiSCs displayed a greater percentage of their open chromatin at promoters and exons, compared with the NPCs and MEFs, and overall, as expected, ESCs had the Review most accessible chromatin, followed by EpiSCs.…”
Section: Chromatin Is Globally More Accessible In Pluripotent Cellssupporting
confidence: 57%
See 1 more Smart Citation
“…Comprehensive mapping of open chromatin regions using FAIRE-seq in 2i-grown ESCs, EpiSCs, NPCs, and MEFs revealed a marked difference between the two pluripotent cell lines, ESCs and EpiSCs, and the two differentiated cell types (Murtha et al, 2015). ESCs and EpiSCs displayed a greater percentage of their open chromatin at promoters and exons, compared with the NPCs and MEFs, and overall, as expected, ESCs had the Review most accessible chromatin, followed by EpiSCs.…”
Section: Chromatin Is Globally More Accessible In Pluripotent Cellssupporting
confidence: 57%
“…MNAse digestion more accessible (Morozumi et al, 2016 ) --DHS-seq more accessible (Deng et al, 2013) --FAIRE-seq more accessible (Murtha et al, 2015) even more accessible (Murtha et al, 2015) RED-seq more accessible (Chen et al, 2014) --ATAC-seq more accessible (Simon et al, 2017;Xu et al, 2017) comparable to serum (Hendrickson et al, 2017;Wu et al, 2016) The epigenome DNA methylation comparable (Melcer et al, 2012) much lower (Marks et al, 2012) active histone modifications slightly higher (Efroni et al, 2008;Hezroni et al, 2011;Morozumi et al, 2016;Qiao et al, 2015;Yellajoshyula et al, 2011) slightly higher (Rahjouei et al, 2017) suppressive histone modifications slightly lower (Ahmed et al, 2010;Efroni et al, 2008;Liu et al, 2015;Loh et al, 2007;Sridharan et al, 2013) slightly lower (Fussner et al, 2011) H3K27me3 slightly lower (Juan et al, 2016)…”
Section: Developmental Cellmentioning
confidence: 99%
“…Transcription of endogenous retroviruses, notably HERVK and HERVH, plays a role in the maintenance of pluripotency. An examination of chromatin in murine ESC using FAIRE similarly demonstrated variation in regions associated with developmental pathways (Murtha et al, 2015). Although not addressed in this study, our analysis of these data also demonstrated enrichment of repetitive elements in mESC compared to MEF (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…While the reasons for these mouse-human differences remain unclear, there are a number of practical advantages that make the naïve state a more desirable research tool. Pluripotent naïve stem cells are characterized by a more open chromatin structure (Murtha et al, 2015), allowing for more efficient genetic manipulation (Buecker et al, 2010; Zwaka and Thomson, 2003). In addition primed cells are prone to greater heterogeneity in gene expression (Bernemann et al, 2011; Gafni et al, 2013; Osafune et al, 2008), making it difficult to obtain unbiased lineage-specific specification.…”
Section: Introductionmentioning
confidence: 99%